2018
DOI: 10.1002/jum.14898
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Low‐Intensity Pulsed Ultrasound‐Treated Dendritic Cells Suppress Tumor Necrosis Factor–Induced Endothelial Inflammation

Abstract: Objectives Endothelial cell inflammation plays an important role in atherosclerosis. Low‐intensity pulsed ultrasonography (LIPUS) exerts an anti‐inflammatory function on endothelial cells, whereas the underlying mechanism has not been fully elucidated. Methods Bone marrow dendritic cells (BMDCs) derived from bone barrow cells were treated with LIPUS, and exosomes secreted into the supernatant were purified. The isolated exosomes were incubated with human umbilical vein endothelial cells (HUVECs) to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…From these DC subtypes, EXO were purified, quantitated and correct size distribution (30–150nm) confirmed by nanoparticle tracking analysis ( Figure 1A ). Further characterization indicates predominant population of EXO, as determined by immunogold-CD63 TEM ( Figure 1B ), immunoblot for Tsg101 (component of Escort1 complex), CD81, B-actin, Alix (Escort Associated Protein) and EXO negative marker GRP94 ( Figure 1C ), as previously reported [ 43 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…From these DC subtypes, EXO were purified, quantitated and correct size distribution (30–150nm) confirmed by nanoparticle tracking analysis ( Figure 1A ). Further characterization indicates predominant population of EXO, as determined by immunogold-CD63 TEM ( Figure 1B ), immunoblot for Tsg101 (component of Escort1 complex), CD81, B-actin, Alix (Escort Associated Protein) and EXO negative marker GRP94 ( Figure 1C ), as previously reported [ 43 ].…”
Section: Resultssupporting
confidence: 80%
“…EXO donor DC subtypes including immunoregulatory DCs (regDCs), immature DCs (iDCs), and immunostimulatory (stimDCs) were generated from bone marrow derived non-adherent cells of C57BL/6 mice, and phenotype and cytokine profiles characterized as follows: regDCs:CD11c +, low MHCII+, low CD86+, low CD80 +and low CD40+ Figure 1A). Further characterization indicates predominant population of EXO, as determined by immunogold-CD63 TEM ( Figure 1B), immunoblot for Tsg101 (component of Escort1 complex), CD81, B-actin, Alix (Escort Associated Protein) and EXO negative marker GRP94 ( Figure 1C), as previously reported [43].…”
Section: Generation and Characterization Of DC Exo Subtypes Prior To supporting
confidence: 81%
“…2s). Previous studies have reported that exosomes are generally enriched with certain speci c marker proteins, such as CD9, CD63, CD81, TSG101 and HSP70 [23,24], with lower expression of some cellular proteins, such as cis-Golgi matrix protein GM130 [25] and endoplasmic reticulum (ER) calnexin [14,15]. Exosomes can therefore be identi ed by western blotting or ow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…2s). Western blotting revealed positive expression of CD63 and TSG101, two of the well-established surface markers for exosomes, and negative expression of calnexin, commonly used as a negative control for extracellular vesicles [14,15] (Fig. 2t).…”
Section: Isolation and Identi Cation Of Exosomes Derived From Cafs Anmentioning
confidence: 99%
“…Here, doxorubicin was delivered into glioma tumors with the help of FUS, while no significant differences in physical features, ultrasound-responsiveness, or specific glioma targeting were observed [82]. Moreover, another modality of ultrasonography called low-intensity pulse ultrasonography (LIPUS) as well as its impact on exosomes was studied by Li and colleagues [83]. Bone marrow dendritic cells (BMDC) were extracted from dead C57BL/6 mice's bone marrow and part of them was treated with LIPUS.…”
Section: Ultrasound (Us)mentioning
confidence: 99%